Technology for maintaining oral care after stroke: considerations for patient-centered practice. (17th November 2022) - Gurgel-Juarez, Nalia; Egan, Mary; Wiseman, Michael; Finestone, Hillel; Flowers, Heather L.
Abstract: Purpose: Activities of daily living including oral care may be challenging after stroke. Some stroke survivors are not able to complete oral care independently and need assistance from healthcare professionals and care partners. Poor oral hygiene may impact stroke recovery and rehabilitation possibly incurring issues such as aspiration pneumonia, malnutrition, and social isolation. The objective of this paper is to outline practical ways to apply oral care technology in daily use for stroke survivors. Materials and methods: We reviewed the literature on i) stroke-related impairments impacting oral care, ii) oral hygiene dental devices, and iii) technology for oral care education. Results: Oral care activities involve integrated skills in the areas of motivation, energy, planning, body movement and sensation, and mental acuity and health. Post-stroke impairments such as fatigue, hemiparesis, and mental impairments may impact oral care activities. Technology may help survivors and caregivers overcome some barriers. Three types of technologies are available for facilitating post-stroke oral care: i) non-powered tools and adaptations; ii) powered oral care tools, and; iii) electronic aids to guide oral care activities. Particular choices should maximise patient safety and autonomy while ensuring accessibility and comfort during oral care tasks. Conclusion: The available device and technologies may help substantially with the accommodations needed for post-stroke oral care, improving the oral health of stroke survivors. Good oral health confers benefit to overall health and well-being and could enhance recovery and rehabilitation outcomes. Nonetheless, more research is necessary to demonstrate the feasibility and effectiveness of technology in stroke contexts. IMPLICATIONS FOR REHABILITATION: Oral care may be challenging after stroke due to patient fatigue, hemiparesis, cognitive impairments, and other impaired body functions. Poor oral hygiene may impact stroke recovery and rehabilitation due to risk of aspiration pneumonia, malnutrition, and social isolation. Powered oral care tools, non-powered tools, and adaptations to non-powered tools are some of the technology available to help overcome post-stroke barriers for oral care. Computer programs and online resources for education and guidance for oral care activities may help improve recommendation uptake and compliance.